A Unique Model for Developing Continuing Education Resources for Health Professionals in Geographically Dispersed Health Organizations. Issue 3 (28th October 2021) - Ohr, Se Ok; Maguire, Dee; Lord, Nina; Talluri, Chitti; Solman, Annette
Abstract: The provision of high quality, equitable, and accessible education resources is a key to supporting continuing professional development (CPD) in health organizations. The Health Education and Training Institute (HETI) and its operational model for districts (District HETI Operational Model), is a novel approach that supports this imperative for over 155, 000 staff working across the state of New South Wales (NSW), Australia. The model uses three principles in education and training development. These include collaborative partnerships, rapid resource development, and effective leadership within virtual teams. A state-wide learning management system has been implemented to support this initiative. Over 451 standardized, education, and training online modules have been developed for medical, nursing and midwifery, dental, allied health, and nonclinical NSW Health employees since 2013. These educational resources are accessible 24 hours a day. Cost-effective online programs have enabled more than 13.6 million learner completions. Program evaluations highlight the value of these resources in providing a positive learning experience. Furthermore, the District HETI Operational Model has been recognized by multiple national and international excellence awards in learning and development. The principles of the District HETI Operational Model apply to other health organizations that may choose to adopt a similar model. Such a model may support equity of access to contemporary, standardized, evidence-based education resources for health professionals working across geographically and clinically diverse environments. Implementation of a similar model for future CPD interventions warrants consideration by practitioners, researchers, and policymakers.